BIODIVERSITY MEASURES - MATHEMATICAL EVALUATION OF VARIOUS INDICES - Manjula Josephine Bollarapu, K.V.S.N. Ramarao, (Chelonian Research Foundation, 2023)
Humans for their personal needs are devastating natural resources resulting in animal habitats destruction. This habitat destruction is resulting in species extinctions. Consequently, it is causing a threat to biodiversity. There is need to preserve biodiversity otherwise it will have serious effects like pollution, change in climatic conditions resulting in severe effects on humans and animals. Hence there is a need to assess biodiversity periodically and alert ecologists and government agencies. To assess biodiversity, there are several mathematical indices developed. Diversity indices provide important information about richness and evenness of species in a community. Hence the aim of this study is to evaluate, analyze various mathematical measures and their applicability to various real-time situations.